PENGARUH PENERAPAN MODEL DISCOVERY LEARNING TERHADAP HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS VIII SMP PEMBANGUNAN LABORATORIUM UNP - Nuri Oktavia (Departemen Matematika, 2021)
Mathematics learning outcomes are needed to determine the ability and understanding of students. The problem in the UNP Laboratory Development Junior High School is that mathematics learning outcomes are still low. This study aims to determine whether the results of learning mathematics using the discovery learning model are better than conventional learning. This type of research is a quasi-experimental design using a Randomized Control-Group Only Design. The research population is all students of class VIII with a sample class of class VIII. A and class VIII. B selected by purposive sampling technique. Learning outcomes test in the form of essay questions was used as a research instrument. From the data analysis, the average value of the experimental class was 65.36 and the control class average was 55.62. The results of hypothesis testing with t-test obtained P-Value = 0.009 or reject Ho because it is less than . So it can be concluded that students who study with the discovery learning model have better learning outcomes than students of class VIII SMP UNP Laboratory Development with conventional learning. Keywords — discovery learning, learning outcomes